2005
DOI: 10.1002/j.2055-2335.2005.tb00362.x
|View full text |Cite
|
Sign up to set email alerts
|

Patients' Understanding of Drug Allergy and Documentation—Is There a Link?

Abstract: Background: Re-exposure to a drug to which one is allergic is a preventable adverse drug event. There is a reliance on the patient to provide accurate information on their allergies for the purpose of complete documentation. Aim: To investigate the relationship between patients' understanding of their drug allergy and documentation of their allergy status in their hospital records. Method: A structured interview of inpatients identified whether they had a drug allergy. Patients were then assessed on their abil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 25 publications
1
3
0
Order By: Relevance
“…Our review of the medical records demonstrated that the majority have poor allergy documentation, with good documentation for only 23.5% of patients. These findings were similar to the findings of a pilot study 12 that reported missing information in EMR. In addition, several patients with several drug allergies had only one of their allergies documented.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our review of the medical records demonstrated that the majority have poor allergy documentation, with good documentation for only 23.5% of patients. These findings were similar to the findings of a pilot study 12 that reported missing information in EMR. In addition, several patients with several drug allergies had only one of their allergies documented.…”
Section: Discussionsupporting
confidence: 90%
“…Of the 20 papers categorized as incomplete, 18 had no information recorded about their allergy status, neither in drug charts nor in medical records. 12 To the best of our knowledge, there are no studies to assess the quality of documentation of drug allergies in pediatric patients in a Saudi medical care setting. Thus, our aim in this study is to evaluate the practice of antibiotic allergies documentation in the electronic medical records (EMR) and determine the validity of physicians’ decisions to hold antibiotics prescriptions.…”
Section: Introductionmentioning
confidence: 99%
“…Although true allergies are uncommon, there have been reports of patients suffering adverse effects following administration of medicines they have been previously identified as causing an allergic reaction [3]. These unnecessary reactions can be avoided by creating a complete documentation of allergies as soon as the patient is admitted to hospital [4]. It is therefore vital that the acknowledged allergy status of the patient is accessible at the time of prescribing and administration of drugs.…”
Section: Introductionmentioning
confidence: 98%
“…[1][2][3] Despite being preventable, the repeated prescribing of known allergenic medications is still common, accounting for 8% to 15% of the medication errors worldwide. 2,[4][5][6][7] In response to the global concern about drug safety, the European Academy of Allergy and Clinical Immunology has recommended the use of drug allergy cards. 8 This method has long been implemented in public hospitals in Malaysia as a strategy to facilitate the communication of patients' drug allergy history, especially during emergency situations in which complete medical records and medication history are usually not available.…”
mentioning
confidence: 99%